„Rut appearance on pavement surface and measurements on motorway A-4 in Macedonia“ - Mijoski G. (BRNO UNIVERSITY OF TECHNOLOGY, FACULTY OF CIVIL ENGINEERING, 2014)
Within The Pavement Management System, transversal roughness - the rut depth of pavement surfaces is one of the indicators for assessing the condition of the roads which determines their driving performance. Since the rut collects and retains water (instead drainage), the depth or amount of retained water on the pavement surface has a crucial influence on the creation of aquaplaning and disorder of traffic safety. The measurements of roughness were made on the motorway A-4 that passes though Republic of Macedonia which is part of the international road E-65 (length 14,2 km) with the measuring apparatus high-speed inertial profiler (The Dynatest Road Surface Profilometer). The evaluation of the condition of the pavement surface in terms of transversal roughness – rut depth was conducted by Slovenian criteria for rut depth (TSC 06.610:2003). The results from the evaluation of the measurements showed that the pavement surface is heterogeneous represented in all three states: good, satisfactory and poor, which means that certain sections of the motorway require repairmen of pavement surface. Rut depths and possibility of creating aquaplaning are in proportional dependence; the greater the rut depth, the greater the amount of water that is retained in them, because the amount of water on the pavement surface is creating conditions for the appearance of aquaplaning. Measures for reducing the risk of aquaplaning are: regular measurement and evaluation of the condition of transversal roughness, taking measures for their rehabilitation, improvement of drainage capability of pavement surfaces and improved coefficient of resistance against sliding.
Keywords: Aquaplaning; inertial profiler; measurements; pavement surface; rut depth; transversal roughness